Anti-plasmid activity of Chlorpromazine in types of antibiotics resistant pathogenic bacteria - Alaa Qasim; Muhsin Ayoub Essa (Al-Qadisiyah Journal of Pure Science, 2021)
This study was performed to evaluate the ability of chlorpromazine compound to cure the plasmids and remove the antibiotic resistance character of multidrug resistance Gram-negative pathogenic bacteria.The curing experiment was done by incubating bacterial strains in nutrient broth with sub MIC concentration of chlorpromazine, and the disc diffusion method was used before and after curing to evaluate antibiotic resistance pattern of bacteria. Synergetic test of chlorpromazine with antibiotics that the studied bacteria showed resistance toward also done.The results showed the ability of chlorpromazine to remove the plasmids from four bacterial genera out of five genera, where the most plasmid removal cases was with E.cloacae, P.aeruginosa, and P.merabilis, and the loss of antibiotics resistance was observed in the same bacterial genera, but P.merabilis showed the most antibiotics resistance losing by three antibiotics out of nine antibiotics that the bacteria were resistant to them before curing. As for the synergistic effect, the compound showed a synergism with only two antibiotic and with the three aforementioned bacterial genera.From results of this study we concluded the possibility of removing bacteria resistance to antibiotics by eliminating plasmids through using chlorpromazine, and the possibility of using this compound in synergism with antibiotics, this will open the way to find new strategies  to treat many diseases caused by resistant bacteria.